Main Anthropogenic Impacts on Benthic Macrofauna of Sandy Beaches: A Review - Afghan Afghan; Carlo Cerrano; Giorgia Luzi; Barbara Calcinai; Stefania Puce; Torcuato Pulido Mantas; Camilla Roveta; Cristina Gioia Di Camillo (Journal of Marine Science and Engineering, 2020)
Sandy beaches provide several ecosystem services such as coastal protection and resilience, water filtration and nutrient mineralization. Beaches also represent a hub for social, cultural and economic relationships as well as educational activities. Increasing urbanization, recreational activities and mechanical beach cleaning represent major anthropogenic disturbances on sandy beaches leading to loss of biodiversity as well as good and services. Information about the impacts of anthropogenic pressures on benthic macrofaunal communities could be useful to assess the environmental status of sandy beaches and to promote a sustainable use of beach ecosystem. Here, scientific articles about three major anthropogenic impacts on sandy beach macrofauna were reviewed to provide the state of knowledge about these impacts, to highlight gaps, to supply considerations about the methodologies and the used indicators and to give insights for future studies. The stressors considered in our review are: 1) trampling, 2) breakwater barriers, 3) mechanical beach cleaning. This review underlined that there are few studies regarding individual human disturbances on sandy beach macrofauna and specifically, there is a lack of sufficient indicator species for the assessment of such stressors. Similarly, the researches have covered specific regions, highlighting the need for such studies in other parts of the world. In particular, the impacts of breakwater barriers on surrounding communities has been found to be given less attention in the literature and there is enough that could be explored.